In vitro cytotoxic effects of DEHP-alternative plasticizers and their primary metabolites on a L929 cell line. (April 2017) - Eljezi, Teuta; Pinta, Pierre; Richard, Damien; Pinguet, Jérémy; Chezal, Jean-Michel; Chagnon, Marie-Christine; Sautou, Valérie; Grimandi, Gaël; Moreau, Emmanuel
Abstract: Phthalic acid esters have been widely used to improve the plasticity of PVC medical devices. They carry a high exposure risk for both humans and the environment in clinical situations. Our study focuses on the cytotoxicity of alternative plasticizers. Postulated primary metabolites were synthesized, not being commercially available. Cytotoxicity assays were performed on L929 murine cells according to the ISO-EN 10993-5 standard design for the biocompatibility of medical devices. The tested concentrations of plasticizers (0.01, 0.05 and 0.1 mg/ml) covered the range likely to be found in biological fluids coming into direct contact with the medical devices.DEHP, DINP andDINCH were cytotoxic at the highest concentration (0.1 mg/ml) for 7 days of exposure. Their corresponding metabolites were found to be more cytotoxic, for the same concentration. By contrast, TOTM and its corresponding metaboliteMOTM were not found to be cytotoxic.DEHA showed no cytotoxicity, but its corresponding monoester (MEHA ) produced a cytotoxic effect at 0.05 mg/ml. In clinical situations, medical devices can release plasticizers, which can come into contact with patients. In vivo, the plasticizers are quickly transformed into primary metabolites. It is therefore important to measure the effects of both the plasticizers and their corresponding metabolites. Standard first-line cytotoxicity assays should be performed to ensure biocompatibility. Graphical abstract: Highlights: All plasticizers induce an action on cell proliferation at 0.1 mg/ml. DEHP, ATBC andDINCH are considered as potentially toxic in the standard EN 10993-5. All plasticizers primaries metabolites cause a decrease in cell viability exceptMOTM . MEHT, MINP, MINCH reduce significantly the cell proliferation at 0.1 mg/ml. MINCH causes a very high inhibition of cell proliferation.